Acute cognitive performance and mood effects of coffee berry and apple extracts: A randomised, double blind, placebo controlled crossover study in healthy humans. (2nd November 2022) - Jackson, Philippa A.; Haskell-Ramsay, Crystal; Forster, Joanne; Khan, Julie; Veasey, Rachel; Kennedy, David O.; Wilson, Alissa R.; Saunders, Caroline; Wightman, Emma L.
ABSTRACT: Background: Polyphenols from coffee berry (chlorogenic acid) and apple (flavanol) have been shown to improve mood and increase cerebral blood flow in healthy humans. These effects may underpin the cognitive effects of polyphenols seen previously. Objective: The aim of the present paper was to extend previous research by investigating the effects of coffee berry at high and low doses when combined with apple extract on cognitive performance and mood. Design: This randomised, double-blind, placebo controlled, crossover trial included 46 healthy males and females, 18–49 years of age (mean age 23 years), consuming: 1100 mg coffee berry extract, 1100 mg coffee berry extract plus 275 mg apple extract, 100 mg coffee berry extract plus 275 mg apple extract or placebo on 4 separate occasions, completing cognitive and mood assessments pre-dose and then again at 1-, 3- and 6 hrs post-dose. Results: Analysis revealed a consistent pattern of alerting effects following 1100 mg coffee berry extract. Limited effects on cognitive function were observed. Specifically, faster peg and ball performance (executive function) was observed following 1100 mg coffee berry plus apple extract and accuracy on the Rapid Visual Information Processing (RVIP) task increased on the third of four repetitions following 1100 mg coffee berry alone. Interestingly, more false alarms on RVIP were observed following the same intervention. Conclusions: In line with previous findings, 1100 mg coffee berry engendered increased arousal. The absence of effects on mood when an apple extract was added, and the potential for the low dose of caffeine within the coffee berry to act synergistically with polyphenols, raise interesting future avenues of research. Abbreviations: Cognitive demand battery (CDB), Profile Of Mood States (POMS), Visual Analogue Scale (VAS), Rapid Visual Information Processing (RVIP)